The Development of Naturalism Intelligence as an Effort to Improve the Quality of Education in Schools - Nur Zaytun Hasanah; Istiqomah Istiqomah; M. Hajar Dewantara (STAI Ma'had Aly Al-Hikam Malang, 2022)
Quality education depends on the vision and mission of the educational institution that was founded. The quality of school education will be low, if the management of Human Resources (HR) has not carried out their duties optimally. Many schools have good accreditation, but there are still few teachers who have not implemented their learning management properly, so that students who should behave well towards their surrounding environment, actually act the opposite. The only way to improve quality education is to develop naturalistic intelligence. The purpose of this study is to interpret the development of naturalism intelligence as an effort to improve the quality of education in schools. This research is a type of qualitative research with a qualitative descriptive research approach. Data collection techniques used are observation methods, documentation methods and interview methods. Data collection techniques used are observation methods, documentation methods and interview methods. The data analysis technique used is Miles, Huberman and Saldana with the stages of data collection, data condensation, data presentation and drawing conclusions. The results showed that to improve the quality of education in schools is to develop students' naturalistic intelligence. The strategy carried out by the STP Khoiru Ummah teacher in developing naturalism intelligence is that students are asked to sense and pay attention to the surrounding environment, students are asked to reflect on everything they sense, then students are invited to think about who created the universe, life, and humans. In conclusion, the policies implemented at STP Khoiru Ummah starting from the methods, curriculum and learning are very in line with Islamic education and refer to the Al-Qur'an and Al-Hadith, then the school should be said to be of high quality. Not only from qualified teachers and principals, but also students become the best generation of intelligent and qualified people.